-3h+4.2=55-11h

Simple and best practice solution for -3h+4.2=55-11h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3h+4.2=55-11h equation:


Simplifying
-3h + 4.2 = 55 + -11h

Reorder the terms:
4.2 + -3h = 55 + -11h

Solving
4.2 + -3h = 55 + -11h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '11h' to each side of the equation.
4.2 + -3h + 11h = 55 + -11h + 11h

Combine like terms: -3h + 11h = 8h
4.2 + 8h = 55 + -11h + 11h

Combine like terms: -11h + 11h = 0
4.2 + 8h = 55 + 0
4.2 + 8h = 55

Add '-4.2' to each side of the equation.
4.2 + -4.2 + 8h = 55 + -4.2

Combine like terms: 4.2 + -4.2 = 0.0
0.0 + 8h = 55 + -4.2
8h = 55 + -4.2

Combine like terms: 55 + -4.2 = 50.8
8h = 50.8

Divide each side by '8'.
h = 6.35

Simplifying
h = 6.35

See similar equations:

| 6+(3x-3)=2 | | 3x+5-3x=4x-2 | | 3x+5-3x=4x-2 | | -10+p/9=-11 | | -9(x+6)=-54 | | 1/5s=2 | | 8x^2-22x-90=0 | | 7mx^2+2nx^2-7my^2-2ny^2=0 | | 7/5-3/8(136/15)=-2 | | 25+4(-4x+5)= | | 14z=0 | | 8/3x^2-5/4x | | 1/2x=11/14+4/7 | | 7/5-3/8(136/15) | | 17-(6x+3)-2x+4= | | ((3(x-4)/4)/4)=4x-4 | | 6a^2+27a-15=0 | | 7x+2y=26 | | 75/3*25= | | 10w-14wv-15w+21v=0 | | 3(x-8)=4(x+2) | | -2[6x+1]=4[x-5]-2 | | -12*(6-4)+2= | | (5/8)(-9) | | 3(x-8)=4x+2 | | -12*6-(4+2)= | | 8ax-6x-12a+9=0 | | 16x=1248 | | (-12*6)-4+2= | | 15-2n=n-1 | | 3/4-7/20 | | -7/6=-2n+7/3n |

Equations solver categories